Trypanosoma cruzi prevalence and clinical forms in blood donor candidates in Brazil Prevalência e formas clínicas de Trypanosoma cruzi em candidatos a doadores de sangue no Brasil - H J Silveira; O N Mozart; A N Norberg; E A Pile (Universidade de São Paulo, 2003)
The prevalence and clinical forms of Trypanosoma cruzi were evaluated among blood donor candidates attended at a general hospital in Rio de Janeiro, Brazil, from January 1997 to April 1999. The investigation was done by means of the indirect hemagglutination test and was confirmed via ELISA. Data were collected from clinical examinations, conventional electrocardiogram, chest radiography and echocar-diography. The results showed that despite Trypanosoma cruzi prevalence of 1.17% (128 patients), mainly in males aged 40 years or over, 70.8% of these patients, mainly males aged 19 to 39 years, demonstrated abnormalities that allowed the diagnosis of cardiopathy and/or esophagopathy. This once again corroborates the importance of Trypanosoma cruzi infection in urban centers. A prevalência e a manifestação das formas clinicas de Trypanosoma cruzi foram avaliadas em candidatos a doadores de sangue atendidos em um hospital geral de Nova Iguaçu, Rio de Janeiro, Brasil, no período de janeiro de 1997 a abril de 1999. A pesquisa sorológica foi realizada por meio do teste de hemaglutinação indireta e confirmada pelo ELISA. Os dados foram coletados considerando os exames clínicos, eletrocardiograma convencional, radiografia de tórax e ecocardiografia. Os resultados demonstraram que, apesar da prevalência ser de 1,17% (128 pacientes), principalmente entre homens com idade igual ou superior a 40 anos, 70,8%, principalmente de homens entre 19 e 39 anos, demonstraram alterações que permitiram o diagnóstico de cardiopatias e/ou esofagopatias, ratificando mais uma vez sua importância nos centros urbanos.